Influence of gtk room application quality on motivation performance, and competence of physical education teachers in surabaya junior high schools - Rokhmawati, Ita Sri; Purwoko, Budi; Hazin, Mufarrihul; Sholeh, Muhamad; Hariyati, Nunuk (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
The purpose of this study was to analyze the effect of the quality of the Ruang GTK application on improving the motivation, performance, and competence of Physical Education teachers. This study uses a quantitative approach with a correlational survey method. The population is physical education teachers totaling 98 people and a sample of respondents as many as 78 people. The data in this study were collected using a Likert scale questionnaire. Data were analyzed using SPSS and SEM statistical software. The results showed that the quality of the Ruang GTK application had a significant effect on improving the motivation, performance, and competence of Physical Education teachers, with the average value of each variable in the high category and low standard deviation. Multiple regression analysis showed that 62.7% of the variation in the three variables was explained by the quality of the application, with high significance (p <0.001). Individually, application quality most strongly influenced motivation (β = 0.52), followed by performance (β = 0.48) and competence (β = 0.46), all of which were statistically significant. Further research is recommended to explore the long-term impact of this application, explore its integration with other platforms, and compare its effectiveness across subjects to strengthen the comprehensive and sustainable development of teacher competencies.